The relationship between a healthy lifestyle and diarrheal disease among children in the penanae health center workplace - Tri Yubiah; Nur Baety; Ira Wati (Journal of Health Technology Assessment in Midwifery, 2022)
Background: Diarrheal disease is a global problem that has become the second leading cause of death in children under five years old. Diarrhea can last for several days. Diarrhea deaths are mainly caused by dehydration due to fluid and electrolytes loss through feces. This study investigates the relationship between a healthy lifestyle and diarrheal disease among 1-5 years children in the Penanae Health Center workplace. This research used a quantitative analytical descriptive method with a cross-sectional approach. The populations were the 110 mothers with children who experienced diarrhea in January-August, while the numbers of samples taken were 52 samples. Based on the results of Clean and Healty Living Behaviour (CHLB) data recorded 52 respondents, including 31 mothers who gave exclusive breastfeeding (59.61%) and 21 mothers who did not give exclusive breastfeeding (40.38%). The CHLB data also recorded that the  30 respondents used clean water (55,76%), while 22 respondents did not use clean water (44.23%). Moreover, there were 19 respondents had handwashing behavior (36.53), while the other 33 respondents did not have handwashing behavior (63.46%). Lastly, the data shows that 34 respondents used hygienic toilets (65.38%), while 18 respondents did not use hygienic toilets (34.61%).